Penerapan Pembelajar Aktif Melalui Teknik Find Thefib Untuk Meningkatan Hasil Belajar Biologi Pada Siswa Kelas XI SMA Jaya Negara Makassar - Nur Amaliah Ahmad; Nova Dwi Pratiwi Sulastri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Research This is class action research( PTK ). The subjects of this study are class XI students of SMA Jaya Negara Makassar.This study aims to describe the improvement of biology learning outcomes through the Find TheFib technique in biology learning for class XI students of SMA Jaya Negara Makassar, with a total of 24 students consisting of 11 men and 13 women. The Find theFib technique is a technique that uses a true and false system, where 2 choices are right and 1 choice is wrong. The research method used is class action research (PTK) with quantitative and qualitative approaches. Data collection using interview instruments, observation sheets and test results. The data analysis techniques in this study use quantitative analysis and qualitative analysis. Based on the results of this research, learning through the Find the Fib technique can increase activities and learning outcomes of Biology in class XI students of SMA Jaya Negara Makassar